THE MULTYREPRESENTATION TEST AS ASSESSMENT AUTHENTIC FOR LEARNING PROSPECTIVE TEACHER PHYSICS - Murtono Murtono (Integrated Lab Journal, 2018)
Concepts mastery is a very important part that must be owned by prospective ofphysics teacher to solve a variety of problems in physics. Multyrepresentation is one of the ways that you can use to explore the ability of understanding the concept. Representation skill is a capability for interpret and apply various concepts in solving the problemsappropriately. Assessment with several different representation formats can provide accurate information the ability of prospective teachers in understanding the concepts of physics.